Study of corrosion properties of carbon steel, 304 and 316L stainless steels in sulfuric acid and their degradation products - KHAMME, Eakapoj; SAKDANUPHAB, Rachsak (Journal of Metals, Materials and Minerals, 2023)
In this study, corrosion properties of carbon steel and stainless steels, and degradation of sulfuric acid by the corrosion mechanism are presented. Carbon steel (CS), 304 stainless steel (SS304), and 316L stainless steel (SS316L) specimens were analyzed through their electrochemical response by using a potentiostat measurement. The specimens were submerged in concentrated 98 wt.% of H2SO4 acid for 0 day to 60 day. The degradation of H2SO4 was determined by its volume change, turbidity, and color due to the corrosion mechanism. Corrosion rate of CS, SS304 and SS316L specimens are 43.237 mm/year, 0.420 mm/year and 0.086 mm/year, respectively. After 60 days, the weight-loss of CS, SS304 and SS316L specimens are 48 wt%, 33 wt% and 0.1 wt%, respectively. Corrosion resistance of the materials are influenced by the passive oxide layer that forms on its surface and associated with electrochemical activity or semiconductive composition. The degradation of H2SO4 acid was observed due to the corrosion process of specimens and related to the turbidity and volume increase while the wt% concentration of H2SO4 acid decreases. In order to make material choices that enable continuous and safe operation of the process, it is important to understand the corrosion mechanism changes.